Economic Dynamics: Theory and Computation - Stachurski, John (Cambridge, Massachusetts; London, England : The MIT Press, 2022)
"A supplement for graduate-level courses on computational and quantitative macro, economic dynamics"
Keywords: Statics and dynamics (Social sciences) -- Mathematical models; Economics -- Mathematical models